(untitled) (Research, Society and Development, 2021)
The aim of this study is to evaluate the condition of integrated solid waste management in municipalities in the Centro-Sul region of Ceará, using the Updated Waste Management Condition Index (ICGRA). This index was developed with 62 indicators arranged in four items: system characteristics, system planning, operational conditions and management alignment with the National Solid Waste Policy and new techniques. The methodological approach was carried out by applying the ICGRA spreadsheet to each of the municipalities studied (Iguatu, Jucás, Cariús, Saboeiro and Quixelô). For this, field visits were carried out in the municipalities, interviews with managers responsible for solid waste management and consultations to available publications, legislation and regulations. From the results obtained, it was found that the conditions of the integrated solid waste management systems of the municipalities studied were classified as Inadequate Management, with non-compliance with the guidelines established by the National Solid Waste Policy and inadequate operating conditions as the main factors that compromised the quality of these systems. it was found that the challenges are still great, with regard to selective collection, only the municipality of Jucás partially implemented this type of collection. It was also found that none of the municipalities surveyed had a public policy aimed at assessing the strengths and weaknesses of their solid waste management systems, which made it difficult for managers to diagnose and, consequently, to plan and implement interventions most urgent public services.